1968
DOI: 10.1161/01.res.22.3.315
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Sympathetic Nerve Projections onto the Canine Heart

Abstract: Major branches from right and left sympathetic ganglia were electrically stimulated while force of contraction was recorded from multiple areas of the right and left ventricles. Stimulation of the stellate ganglia generally elicited alterations in force of contraction from all test segments, but excitation of selected nerve trunks induced responses in highly localized regions of the heart. Ablation of narrow strips of epicardium resulted in obliteration of contractile responses in specific, highly localized re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0

Year Published

1969
1969
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(51 citation statements)
references
References 6 publications
1
50
0
Order By: Relevance
“…We obtained the positive chronotropic and dro motropic responses to discrete intracardiac sympathetic nerve stimulation independently (11). On the other hand, an excitation of the extracardiac individual nerve trunks in the car diac plexus induces discrete responses in local ized regions of the heart (4,29,30). After se quential dissection around the major cardiac vessels of the dog heart, the resulting deficits in the responses to ansa subclavia stimulation indicate that parallel, but distinct, sympathetic efferent fibers project to the automatic, con ductile, and contractile tissues (10).…”
Section: Discussionmentioning
confidence: 99%
“…We obtained the positive chronotropic and dro motropic responses to discrete intracardiac sympathetic nerve stimulation independently (11). On the other hand, an excitation of the extracardiac individual nerve trunks in the car diac plexus induces discrete responses in local ized regions of the heart (4,29,30). After se quential dissection around the major cardiac vessels of the dog heart, the resulting deficits in the responses to ansa subclavia stimulation indicate that parallel, but distinct, sympathetic efferent fibers project to the automatic, con ductile, and contractile tissues (10).…”
Section: Discussionmentioning
confidence: 99%
“…3) MI animals underwent the infarction procedure described above. 4) The 90-s group was included to provide an appropriate sham operation to control for nerve injury during the ligation procedure, because cardiac nerve bundles run along major arteries and ligation of the LAD may crush nerve bundles from both stellate ganglia (27). These animals were subjected to thoracotomy and tightening of the LAD ligature for 90 s and then reperfusion and closure of the incision.…”
Section: Induction Of Infarctionmentioning
confidence: 99%
“…Normal atria exhibit a heterogeneous distribution of vagal and sympathetic innervation. 18,21,27 An increased dispersion of atrial refractoriness has been observed in animal models of AF 2,6,7,28 and humans with paroxysmal AF. 9 Increased regional dispersion of AFCL appears to be an important independent determinant of electrophysiological remodeling and is observed even after shortening of atrial refractoriness caused by rapid pacing has stabilized.…”
Section: Role Of Sympathetic Innervation In Electrical Remodeling and Afmentioning
confidence: 99%